La construction symbolique de l'identité nationale française dans les discours de la campagne présidentielle de Nicolas Sarkozy - Angeliki Koukoutsaki-Monnier (Communication)
Using an ethno-symbolic approach, this article explores how Nicolas Sarkozy redefined national identity in his public speeches from his nomination as the official UMP candidate in January 2007 until the May 2007 French presidential elections. The successful candidate put forth a consensual version of the French national identity that equates it with both republican and universal values while evacuating any and all references to sociobiology.